PERAMALAN TINGKAT INFLASI DI INDONESIA TAHUN 2022 MENGGUNAKAN METODE HOLT-WINTERS DENGAN OPTIMASI GOLDEN SECTION - Vera Sutriani (UNEJ e-Proceeding, 2022)
Inflation is a significant indicator of maintaining the stability of a country's economy, so it is essential to control the inflation rate through economic policies. Thus, necessary to estimate the rate of inflation. Estimates in mathematics are called forecasting. This research will focus on forecasting the inflation rate in Indonesia using a quantitative forecasting method, namely the Holt-Winters exponential smoothing with parameter optimization using the Golden Section. Formulations of this research are: (1) Which method is better for forecasting the inflation rate in Indonesia in 2022? (2) What are the results of forecasting? This research is applied research. The object is data on the inflation rate in Indonesia period 2017-2021, obtained from the Bank Indonesia website. Methods This research is a literature study collecting information related to the Holt-Winters method and the optimization of the Golden Section. The results of this study are: (1) the Holt-Winters Multiplicative method with the optimization of the Golden Section is better than the Holt-Winters Additive method with the optimization of the Golden Section to predict the inflation rate in Indonesia in 2022; (2) The forecasting results are as follows: 1.94%; 2.20%; 2.37%; 2.74%; 3.08%; 3.17%; 3.20%; 3.21%; 3.21%; 3.21%; 3.13%; 3.28%. Keywords: Inflation, Forecasting, Holt-Winters, Golden Section